FDP Crisis or Liberalism Crisis in Germany? (Economic and Political Thought, 2012)
The article analyzes the causes of the crisis in the German liberal party– Freie Democratische Partei (FDP). In the past, the party played animportant role in the history of the Federal Republic of Germany and itsrepresentatives held the key political posts, e.g. Hans Dietrich Genscher.Since the 1990s, the FDP has been in crisis in spite of its success in the 2005election to Bundestag. The author asks a question about the reasons of thecrisis. The first of them he identifies is the actual lack of personalities suchas Genscher and Graff Otto von Lambsdorff used to be. Another reason isa general crisis of parties in Germany; the FDP suffers from it in particularbecause it does not have a substantial group of a stable party electorateand so loses its supporters to other parties’ advantage. The FDP made anerroneous attempt to profile itself by postulating lower taxes. But in theunfavorable economic situation at the time and in coalition with ChristianDemocrats, it was unable to implement it and started to be perceived as aneoliberal party. With the increasing economic crisis, growing uncertainty ofthe society and people looking for support in the state and its benefits, theparty started to be associated with the negative trends in the contemporaryeconomy. In such an unfavorable constellation, the attempts to warm theparty’s image and to show that it is not interested in gaining profits but infreedom in its broad sense have not been really effective.